Sexual abuse is more frequently reported by IBS patients than by patients with organic digestive diseases or controls. Results of a multicentre inquiry. French Club of Digestive Motility - Delvaux, M; Denis, P; Allemand, H (European journal of gastroenterology & hepatology, 1997)
The aim of this multicentre inquiry was to evaluate the prevalence of sexual abuse among IBS patients consulting a gastroenterologist, in comparison to healthy controls and patients with organic digestive diseases. Patients with irritable bowel syndrome (IBS; Rome Criteria) were included by eight university hospitals (n = 196; 41.2 +/- 20.6 years; sex ratio (M/F) = 0.23). Control groups were: (i) patients consulting for the follow-up of non-neoplastic organic digestive diseases (n = 135; 41.5 +/- 17.0 years; 1.21); (ii) patients attending ophthalmology units (n = 200; 43.8 +/- 20.7 years; 0.81); (iii) healthy subjects seen in centres of the National Health System (n = 172; 40.3 +/- 16.3 years; 0.83). Each patient filled in an anonymous questionnaire, without help. Prevalence of sexual abuse in the various groups was compared by the chi 2 test. Sixty-two instance of sexual abuse (55 females, 7 males) were recorded among the 196 IBS patients (31.6%); 8 cases of verbal aggression, 4 of exhibitionism, 11 of sexual harassment, 22 sexual touches, 17 rapes. The prevalence of sexual abuse was 14.0% for the patients with organic digestive diseases (P = 0.0005 vs. IBS), 12.5% among ophthalmology patients (P < 0.0001) and 7.6% in healthy controls (P < 0.0001). Sexual abuse was accompanied by physical abuse in 23 IBS patients and 19 patients from control groups (not significant). Twenty-six IBS patients reported isolated physical abuse (14.7%) versus 40 from control groups (8.8%; P = 0.041). There was a significant trend towards more severe attacks of abuse among IBS patients than in others. This study confirms the high prevalence of sexual abuse among IBS patients consulting in Gastroenterology. Some of these patients would benefit from appropriate therapy. (In the majority of cases, this will be psychotherapy.)